Access to Land Influencing the Urban Development of Egypt - MOHAMED RASLAN; HANY AYYAD (Journal of Contemporary Urban Affairs, 2019)
The paper seeks to assess the impact of access to the land of Egypt on urban development in an attempt to identify policies and laws that can be categorized as a catalyst in urban conflict. A systematic review of Data on land tenure environment of Egypt, land access, land governance and tenure security, the actors involved in these processes, their roles, the land tenure related challenges they face and measures that can be taken to address these challenges was collected at country level.  In the context of Egypt, Access to land is deemed with obstacles confronting beneficiaries and legal procedures that uncover dispute. By investigating the land tenure environment, conclusions could be drawn on how to improve the systems so that they can be used as development tools that decrease the probability of conflict to happen. Furthermore, by understanding how access to land plays a crucial role in urban development patterns, we can allocate recommendations for more sustainable developments.